1990
DOI: 10.1111/j.1151-2916.1990.tb05146.x
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening of Glass by Sol‐Gel Coatings

Abstract: The affects of alkoxide-derived coatings on the bending strength of silica glass were investigated. For densified coatings, increases in strength of 120% to 130% were found. A model of the strengthening process, based on the filling-in and partial healing of surface flaws, is proposed. The model accounts for the temperature dependence of strengthening, the insensitivity of strengthening to the size of oligomers in the coating solution, and the insensitivity of strengthening to the thickness of the coating. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
1
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 20 publications
1
36
1
1
Order By: Relevance
“…The influence of Si02 coatings on the bending strength of fused silica was examined by Fabes et al [64]. The surface of a sampie was at first damaged and weakened by scratches and flaws and then was repaired reasonably by a Si02 coating.…”
Section: Strengthening Coa Tlngsmentioning
confidence: 99%
“…The influence of Si02 coatings on the bending strength of fused silica was examined by Fabes et al [64]. The surface of a sampie was at first damaged and weakened by scratches and flaws and then was repaired reasonably by a Si02 coating.…”
Section: Strengthening Coa Tlngsmentioning
confidence: 99%
“…Different materials for such coatings have been proposed like sol-gel (Fabes et al 1986;Fabes and Uhlmann 1990;Fabes and Berry 1990;Chen et al 1992;Wang and James 1991) or polymers (Chen et al 1995;Hand et al 1998;Wang et al 1997;Kingston and Hand 2000;Hand et al 2003;Briard et al 2005;Roach et al 1988;Swanson et al 1987). In both cases, actual impregnation of the flaws by the coating is required for significant strengthening.…”
mentioning
confidence: 97%
“…Many mechanisms have been proposed for glass strengthening by coatings (Fabes and Uhlmann 1990;Fabes and Berry 1990;Wang and James 1991;Hand et al 1998Hand et al , 2003Roach et al 1988) but only few of them discuss the impact of the mechanical properties of the coating on glass strengthening. Hand et al (1998) suggested that the value of the Young's modulus of the confined coating can become similar to the glass modulus because of Poisson ratio effects.…”
mentioning
confidence: 98%
“…Another way to improve the strength of the glasses is to apply on their surface the protective coating obtained by the chemical reaction during the formation of these coating. Typical coatings on a glass are sol-gel coating made on the basis of organosilanes and coating hybrid organic-inorganic which have been resulted from the chemical reaction [8]. The increase in the mechanical properties of glasses can be achieved by the coating of zirconium oxide (ZrO 2 ) [9].…”
Section: Introductionmentioning
confidence: 99%